Mapping of SDGS in the engineering and computer science curriculum at Universiti Teknologi MARA / Zainab Mohd Noor, Masria Mustafa and Rozzana Mohd Said - Mohd Noor, Zainab; Mustafa, Masria; Mohd Said, Rozzana (Universiti Teknologi MARA, 2023)
Higher Education Institutions (HEIs) are central players in the achievement of the SDGs. As many HEIs strive to embrace sustainability as one of the university's core values and increase the visibility of the institutions globally, there is a need to explore the embedded curriculum framework of SDGs into programs and courses offered at Universiti Teknologi MARA (UiTM). This study is to determine the percentage of SDGs elements that have been incorporated into the university curriculum. The methodology used includes data collection using the university online syllabus system for the science and engineering and technology fields, namely all the engineering fields, Civil, Mechanical, Electrical, and Chemical Engineering, and Computer Sciences, and analyzing the results for in-depth interpretation and dimension analysis. A total of 520 courses were analyzed. The results showed that three SDGs were not addressed by the curriculum. The highest percentage of courses were mapped to SDG9 (25%) followed by SDG4 (15%), SDG 11 and SDG12 at 12%. The SDGs elements were found to be highly incorporated in mechanical engineering compared to other disciplines. The finding helps the understanding of the baseline status of sustainability in the university curriculum and opportunities to improve. It is suggested that another review needs to be executed to include the three SDGs which were addressed in the current curriculum. When all SDGs are addressed, the outcomes of the curriculum will be global graduates who are knowledgeable and responsible in ensuring a harmonized and peaceful future.